Communication in IT adoption: The use of infographics in the case of Citizen Observatories - Pires, Patrícia (2019)
In this presentation we explore the potential of infographics as a communication tool to increase awareness and citizen participation in Citizen Observatories (COs). We present and discuss a project developed through the use of infographics, aiming to contribute to the dissemination of this novel concept and fostering its adoption, as developed and funded by the European Commission. In a first section the concept is presented and the relevance of communication and citizen engagement in the adoption of COs is argued. In a second section the concept of infographics is discussed, as a relevant resource for communication and citizen engagement. In the third section the infographics project developed by the team, with desktop and mobile versions, is presented and explained. In a fourth section the results from a survey assessing the user experience with the infographic, with a sample of journalism and communication students from 9 different nationalities, are presented.